Legal enforcment of illegal trade in protected wild animals in The Region Resor Konservasi XXIII Cirebon - Anjayani, Risa; Faizah, Ade Lulu Nurul; Khoerunisa, Aolia; Henda, Rd.; Gumilang, Iwan G. (International Journal Labs, 2024)
This study aims to analyze the legal enforcment of illegal trade in protected wild animals in the Region Resor Konservasi XXIII Cirebon. Data collection techniques were carried out by interviewing one of the KSDA employees of conservation resorts in the region. The data were analyzed qualitatively and presented descriptively. The results show that the illegal trade of protected wildlife poses a serious threat to the sustainability of animals in Indonesia because illegal trade is a major factor in the decline of protected species in Indonesia. Law enforcement is the government's effort to minimize the occurrence of illegal trading in protected wildlife that needs to be improved by encouraging regulations at the regional and central levels for the protection of species that have not been included in protected status.